Discussion: COVID-19`s impact on sports and athletes - Scerri, M.; Grech, V. (German Journal of Exercise and Sport Research, 2021)
As major sport events have been cancelled and postponed in response to coronavirus disease 2019 (COVID-19), the necessity to protect and provide a holistic approach to the professional athlete has never been greater. To do so one must understand the negative consequences for athletes in relation to the cancellation and postponement of such events caused by a communicable pandemic. The aim of this paper is to give a brief overview of how athletes were affected during the current COVID-19 pandemic. It will also discuss the role of athletes during a pandemic. Athletes like other celebrities can be role models.They can encourage appropriate behaviours including social distancing to help stall the spread of the virus through social media.The article ends with a short discussion on the resumption of sports after lockdown. In such a context of uncertainty, maximum caution is needed for resumption of sports to ensure a smooth return to previous high levels of training and fitness.